2022
DOI: 10.1097/cm9.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity, β cell function, and adverse pregnancy outcomes in women with gestational diabetes

Abstract: Background: The potential impact of b cell function and insulin sensitivity on adverse pregnancy outcomes in women with gestational diabetes mellitus (GDM) remains uncertain. We aimed to investigate the association between b cell dysfunction, insulin resistance, and the composite adverse pregnancy outcomes. Methods: This observational study included 482 women diagnosed with GDM during pregnancy. Quantitative metrics on b cell function and insulin sensitivity during pregnancy were calculated using traditional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[27] Two Chinese studies also found that increasing IR in the late second trimester might be associated with an increased risk of adverse pregnancy outcomes in women with GDM. [28,29] In this issue of the Chinese Medical Journal, the study by Shen et al [30] assessed the association of b-cell function and insulin sensitivity with the risk of adverse pregnancy outcomes among Chinese women with GDM, and also evaluated the potential impact of different pathophysiologic patterns on adverse pregnancy outcomes of GDM. This observational study included 482 Chinese women diagnosed with GDM.…”
mentioning
confidence: 99%
“…[27] Two Chinese studies also found that increasing IR in the late second trimester might be associated with an increased risk of adverse pregnancy outcomes in women with GDM. [28,29] In this issue of the Chinese Medical Journal, the study by Shen et al [30] assessed the association of b-cell function and insulin sensitivity with the risk of adverse pregnancy outcomes among Chinese women with GDM, and also evaluated the potential impact of different pathophysiologic patterns on adverse pregnancy outcomes of GDM. This observational study included 482 Chinese women diagnosed with GDM.…”
mentioning
confidence: 99%